Eco-friendly synthesis of chitosan NPs from Fioria vitifolia (L.) L: Potential to antibacterial, antioxidant, cytotoxicity properties of HepG2 cells and their evaluation of safety on Zebrafish embryo - Mohamed Imath; Chinnasamy Ragavendran; Chinnaperumal Kamaraj; Ramalingam Karthik Raja; Gholamreza abdi (Results in Engineering)
Antibiotic-resistant microbes are becoming more common, which is a serious healthcare issue that has a huge economic impact on the whole population. The aim of present study was examined antibacterial, antioxidant, antibiofilm and cytotoxicity of liver cancerous cells using Fioria vitifolia mediated chitosan nanoparticles (FV-CNPs). Thus, the biosynthesized of CNPs were characterized using UV, XRD, FTIR, FESEM, and EDX to describe their morphology. The synthesized FV-CNPS study confirms UV–Vis spectral peaks at 320 nm. The XRD pattern showed prominent peaks at 2θ locations, confirming the hexagonal wurtzite structure. EDX was analysis confirmed the presence of chitosan in crystalline form for synthesized nanoparticle. Based on the results, FV-CNPs have an oval form and are mostly made of chitosan and oxygen. F. vitifolia synthesized CNPs exhibited the greatest growth inhibition against S. aureus (27.2 mm) and K. pneumoniae (25.1 mm). Crystal violet was used to observe the growth of biofilms in the presence of different CNPs concentrations in order to quantify the antibiofilm action of CNPs. Also, Antioxidant assay reveals 74 % of DPPH scavenging activities at 100 μg/mL concentration. Using the MTT Assay, the dose-dependent response of FV-CNPs against HepG2 cells was determined, and an IC50 value of 59.41 µg/mL was obtained. Finally, the toxicity test conducted on zebrafish eggs revealed that bending bodies only became visible at levels exceeding 100 μg/mL. This is first-hand information of present study indicates that F. vitifolia extract-using phyto-synthesized CNPs might serve as a biomedical- multifunctional applications in the future.